The first pterosaur pelvic material from the Dinosaur Park Formation (Campanian) and implications for azhdarchid locomotion - Gregory F. Funston; Elizabeth Martin-Silverstone; Philip J. Currie (Canadian Science Publishing, 2017)
A partial pterosaur pelvis from the Campanian Dinosaur Park Formation of Canada adds to our knowledge of Late Cretaceous pterosaurs. The pelvis is tentatively referred to Azhdarchidae and represents the first pelvic material from a North American azhdarchid. The morphology of the ilium is bizarre compared with other pterosaurs: it is highly pneumatized, the preacetabular process tapers anteriorly, and muscle scars show that it would have anchored strong adductor musculature for the hindlimb. The acetabulum is deep and faces ventrolaterally, allowing the limb to be positioned underneath the body. These features support previous suggestions that azhdarchids were well adapted to terrestrial locomotion.